ANALISA MANAJEMEN OPERASIONAL DAN HUBUNGAN PELANGGAN TERHADAP PENGELOLAAN KUALITAS PRODUK NESTLÉ INDONESIA INDONESIA - Devina Wistiasari; Golan Hasan; Adeline Adeline; Erika Erika; Melissa Lestari; Nadiya Nur Arafah (Jurnal Ekonomi dan Bisnis (EK dan BI), 2023)
The majority of companies have implemented various operational management strategies to facilitate monitoring of daily business operations and provide estimates of how the company should run without any problems, for example when COVID-19 occurred. Nestlé Indonesia is a company that produces a variety of food and beverage products with emphasis on nutrition and health. However, over time, when the impact of the spread of the Covid-19 virus hit all countries in the world, including in Indonesia since early March 2020, this situation finally forced the Nestlé Indonesia company to make strategic changes in managing its operations and relationships with customers. The research method uses a type of qualitative research that examines and summarizes information data obtained through books, articles, magazines, news, and so on and then analyzes theoretical materials through literature study with the results of the analysis in the form of descriptive. The results show that before, during and after the pandemic, Nestlé Indonesia continued to maintain product quality due to increased consumer demand for nutritional products. The Nestlé Indonesia company remains dedicated to providing customers with responsible and reliable information, creating a stronger customer database through the Nestlé Indonesia Friends website and also providing attractive offers to maintain good customer relations.